Analisis Data Angin Permukaan Di Bandara Sam Ratulangi Manado Menggunakan Metode Windrose - Tulandi, Djeli A; Tumangkeng, Jeane Verra; Tumbelaka, Febrianty Emanuella Alexandra (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
Research on surface wind patterns was carried out in minimizing the potential for aircraft accidents at Manado’s Sam Ratulangi Airport. Paying attention to wind direction and wind speed data that is easy to change, we need a system that can predict the direction and speed of the wind when take-off, cruising and landing. Sam Ratulangi Airport uses an application/software that can predict wind direction and speed. The method used in solving the above problems is by using the wind rose method. The results of research conducted using the wind rose method and data from 2002 – 2017 (for the past 15 years) show that the dominant surface wind pattern of the Sam Ratulangi Airport is blowing from 1120 – 1570 (Southeast) with a percentage of 15,60% and wind speed dominant (most) 7 – 11 knots with a percentage of 8,73%. In the future or in the following years from February – May the wind direction is expected to be more dominant towards the North West/North, from June – August the wind direction is expected to be more dominant towards the South, September – October is expected to be more dominant to the Southeast, November – January is expected to be more dominant towards the West.